2020
DOI: 10.1016/j.jormas.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Facial pressure ulcers in COVID-19 patients undergoing prone positioning: How to prevent an underestimated epidemic?

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 8 publications
0
72
1
21
Order By: Relevance
“…There were 4 studies [ 12 , [24] , [25] , [26] ] (3 case reports and 1 case-control study) identified. It was ascertained that the main sites of pressure injuries were on the forehead, chin, cheeks, lips and chest ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 studies [ 12 , [24] , [25] , [26] ] (3 case reports and 1 case-control study) identified. It was ascertained that the main sites of pressure injuries were on the forehead, chin, cheeks, lips and chest ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a short period of time since the recent COVID-19 outbreak, there have been a multitude of non-pulmonary complications reported. Perrillat et al [10] recently published their experience of two patients with mainly cheek ulcers after prolong intubation and prone positioning and highlighted the issue of facial ulcers in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The checklist developed had patient preparation activities for prone position as an initial step (24) . As it was aimed at patients with COVID-19, the first action described was the complete dressing with relevant personal protective equipment (PPE) (3)(4) , followed by the assessment of the entire ventral region of the body, correct skin protection with multilayer silicone foam devices, removal of electrodes from the anterior region of the chest and positioning on the upper limbs, adequacy of cushions in the anterior region of the scapular line and pubic symphysis (25)(26)(27) .…”
Section: Study Protocolmentioning
confidence: 99%
“…From the second to the sixth step of the checklist, actions were included that must be performed immediately after positioning in prone position and at each rotation of the upper limb positioning. The second step, related to head care, begins with the bed positioning in reverse Trendelenburg at 30º (26) , in addition to lateralization, rotation of the head position on a cushion to the side of the upper limb that is elevated (24,(29)(30) . Other procedures present in this step are eye care (30) , in addition to the precautions for fixing the orotracheal cannula and enteric tubes, which must be centralized in the oral cavity (27,(30)(31)(32)(33) .…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation